Globalization and digitalization: The challenges to environmental sociology - Yanitsky, Oleg (Advances in Social Sciences Research Journal, 2019)
Our world is in a transition to the Fourth scientific and technological revolution (in other terms, to the digital age). This transition generates the deep transformations in all spheres of natural and social life, and the overall trend of them is the turning of our world into very mobile and uncertain entity with permanently changing disposition of competing forces and the transformation of socio-ecological organisms built in the global ‘Internet galaxy’s network system. An uneven transition of these organisms to the digital world aggravates the studies of these multi-sided global social ecosystems. All these transformations is a challenge to natural, social and technical sciences, the challenge that required a new creative approach to the analysis of such permanently mobile and uncertain socio-ecological structure and to a set of such novelties as virtualization of social life, fundamental changes in a primary eco-structure, new regularities in the biosphere turnover, the hybridization of socio-ecological structures and processes, the metabolic processes and their tempo-rhythms, designing of transboundary socio-ecological structures and many other new phenomena deserving their critical analysis. The article is relied upon the analysis of Russian and foreign research in environmental sociology, on the study of the projects of transboundary ecosystems, and on the personal experience of the author.